The effect of physical exercise on body fat, metabolic health indicators and cardiorespiratory fitness in overweight sedentary women - Kolunsarka, Iiris (2020)
Introduction. Physical activity, sedentary behavior and overweight have been widely studied in health-related research. The guidelines for physical activity were updated in 2018, emphasizing the need for the reduction of sedentary behavior and thus its effects on health. It is commonly accepted that physical activity is related to weight management, cardiorespiratory fitness and healthier blood lipid profile. The purpose of this current work was to study health-effects of the eight-week exercise-intervention, following the official guidelines, within overweight sedentary females. Methods. This study was done as a part of a larger RCT-study, in which the health effects of combined sauna-bathing and exercising were studied. The original study consisted of 49 participants, but in this study only the overweight females were included (n=37). The participants were randomly divided into a control group (no-intervention, n=13) and an experimental group (exercise-intervention, n=24). The participants age was 49 ± 8.7 yrs., BMI 31.9 ± 3.3 kg/m2, height 167 ± 7 cm and body mass 89.1 ± 13 kg. The pre- and post-measurements were conducted with both groups eight weeks apart. The measurements included a body composition measurement with DXA, an indirect VO2max -test and a fasting blood sample to determine total cholesterol, HDL, LDL, triglycerides and blood glucose. Both groups were instructed to follow their normal daily routines and eating habits. The exercise training intervention included training sessions three times a week for one hour at the time. The design of the training program followed the official guidelines for physical activity. Each training consisted of 10-minute warm-up, 20-minute strength training and 30-minute endurance training, for a total of 150 minutes of exercise in a week. Results. Fat mass (-1.5 ± 1.5 kg), fat percent (-1.1 ± 1.1 %) and android (central adiposity) fat mass (-0.2 ± 0.2 kg) decreased and VO2max (+4.2 ± 5.7 ml/kg/min) increased in the experimental group compared to the control group between the pre- and post-measurements (p<0.05). No changes were observed in metabolic health indicators or in fat distribution. Conclusion. The main finding was that guideline-based exercise intervention is an effective way to decrease both total fat mass and android fat mass. In addition, an important finding was that during exercise-induced weight-loss, it is possible to maintain fat-free mass unchanged. No changes were observed in metabolic health indicators or in fat distribution, which might be due to short intervention duration or close to normal blood lipid values in the pre-measurements.